THE ROLE OF AGE AND CULTURE IN UNDERSTANDING SOCIAL AND EMOTIONAL PROCESSES IN DAILY LIFE. (16th November 2018) - Arredondo, C; Luong, G; Fingerman, K
Abstract: Older adults generally report more positive and less negative social interactions, which are associated with increases in emotional well-being (Luong, Charles, & Fingerman, 2011). These findings, however, are based on research that is conducted with predominantly White samples. It is therefore pertinent to examine potential cultural variation in these social and emotional processes. Indeed, research demonstrates that positive social interactions, such as emotional support, have more beneficial effects for people from collectivistic cultures compared to those from individualistic cultures. The current study examined the extent to which the buffering effects of emotional support on the association between interpersonal stressors and daily affect varied with age and cultural group (Latinos vs. European Americans). A total of 264 European American and Latino participants, ranging from 65 to 90 years (M = 74.15 years, SD = 6.57 years), completed four days of ecological momentary assessments as part of the Daily Experiences and Well-Being Study (DEWS). Participants reported whether they received emotional support, experienced an interpersonal stressor, and their positive and negative affect each day. Multi-level models tested the extent to which age and race moderated the effects of emotional support and interpersonal stressors on daily affect. No significant interactions emerged for age. However, a significant 3-way interaction (interpersonal stressor x emotional support x race) showed that on days when Latino older adults experienced an interpersonal stressor and received emotional support, they reported significantly less negative affect compared to European American older adults. Implications for minority aging and well-being will be discussed.